Nanofiber capsules for minimally invasive sampling of biological specimens from gastrointestinal tract. (1st July 2022) - John, Johnson V.; McCarthy, Alec; Su, Yajuan; Ackerman, Daniel N.; Shahriar, S.M. Shatil; Carlson, Mark A.; Reid, St. Patrick; Santarpia, Joshua L.; Zhu, Wuqiang; Xie, Jingwei
Abstract: Accurate and rapid point-of-care tissue and microbiome sampling is critical for early detection of cancers and infectious diseases and often result in effective early intervention and prevention of disease spread. In particular, the low prevalence of Barrett's and gastric premalignancy in the Western world makes population-based endoscopic screening unfeasible and cost-ineffective. Herein, we report a method that may be useful for prescreening the general population in a minimally invasive way using a swallowable, re-expandable, ultra-absorbable, and retrievable nanofiber cuboid and sphere produced by electrospinning, gas-foaming, coating, and crosslinking. The water absorption capacity of the cuboid- and sphere-shaped nanofiber objects is shown ∼6000% and ∼2000% of their dry mass. In contrast, unexpanded semicircular and square nanofiber membranes showed <500% of their dry mass. Moreover, the swallowable sphere and cuboid were able to collect and release more bacteria, viruses, and cells/tissues from solutions as compared with unexpanded scaffolds. In addition to that, an expanded sphere shows higher cell collection capacity from the esophagus inner wall as compared with the unexpanded nanofiber membrane. Taken together, the nanofiber capsules developed in this study could provide a minimally invasive method of collecting biological samples from the duodenal, gastric, esophagus, and oropharyngeal sites, potentially leading to timely and accurate diagnosis of many diseases. Statement of significance: Recently, minimally invasive technologies have gained much attention in tissue engineering and disease diagnosis. In this study, we engineered a swallowable and retrievable electrospun nanofiber capsule serving as collection device to collect specimens from internal organs in a minimally invasive manner. The sample collection device could be an alternative endoscopy to collect the samples from internal organs like jejunum, stomach, esophagus, and oropharynx without any sedation. The newly engineered nanofiber capsule could be used to collect, bacteria, virus, fluids, and cells from the abovementioned internal organs. In addition, the biocompatible and biodegradable nanofiber capsule on a string could exhibit a great sample collection capacity for the primary screening of Barret Esophagus, acid reflux, SARS-COVID-19, Helicobacter pylori, and gastric cancer. Graphical abstract: Image, graphical abstract